UPAYA DINAS SOSIAL TERHADAP ORANG-ORANG BERKEBUTUHAN KHUSUS (DISABILITAS) DI KABUPATEN MERAUKE - Y Budiman; Farida Romaito Pohan; Aminah Aminah (Universitas Islam Darul Ulum Lamongan, 2021)
The objectives and scope of this research are, among others, to find out how the efforts of the social services in carrying out their duties in dealing with people with special needs (disabilities) and to find out what supporting and inhibiting factors are in the process of implementing Regent Regulation number 52 of 2016 article 13 paragraph ( 2). The research method used in this research is descriptive qualitative. The results of this study include: the rights of persons with disabilities are still not being considered such as education, housing worthiness, lack of social services, health including accessibility to disabled services. Based on the results of the research, it can be concluded that in an effort to empower persons with disabilities, the government, in this case the social service, has made several efforts, including: providing assistive devices, providing social assistance to each person with disabilities both inside and outside the institution, and the government providing opportunities for persons with disabilities to participate in banana chips making training in Malang as an effort to open their own business. Supporting factors in this study include family and community support and inhibiting factors, including the limited government budget to allocate funds for the provision and accessibility of disability aids.